Examining Correlates of Math Anxiety among Single-Sex and Co-Educational Schools in Nigeria (Global Journal of Human-Social Science, 2012)
A global view of Mathematics as a subject reveals that it is widely recognized as a problem area and most students have phobia for it In view of this the present study examined correlates of math anxiety among single-sex and co-educational schools in Nigeria The study adopted an ex-post facto descriptive survey research design and a total of 450 participants were randomly sampled for the study 153 34 males and 297 66 females with their ages ranging between 16years and 24years Mean age was 16 2years SD 1 8 Validated self-reported measures were used for data collection and three hypotheses were tested in the study Gender correlated significantly negatively p 001 r - 216 while conception about mathematics and age correlated significantly positively with math anxiety respectively p 05 r 103 114 Other variables of age assertiveness emotional intelligence need achievement motivation life satisfaction and self-esteem did not have significant correlation with math anxiety
Keywords: Single-sex; Co-educational; Math Anxiety; South-western